KLASIFIKASI PENJUALAN OBAT PERTANIAN LARIS DAN KURANG LARIS PADA UD.CAHAYA TANI MENGGUNAKAN METODE DECISSION TREE - nur ida nurhidayati; alim alimuddin (Infotek: Jurnal Informatika dan Teknologi, 2019)
Pesticides are chemicals or chemicals used to kill pests in plants that can inhibit plant growth so that they have an impact on poor yields. UD. Cahaya Tani is one of the drug stores in Moyot Village, Sakra Sub-district, which provides various kinds of medicinal drugs needed by farmers in Moyot Village, Sakra, Sakra, East Lombok. The purpose of this study is to classify the types of drugs which are included in the best-selling category and are not in demand. In this case using the classification method of data mining by applying the decission tree method. Where this method works by forming a decision tree. Based on the results of tests that have been carried out by applying 10 cross validation, the highest accuracy is obtained in the K-Fold Validation 8 with a value of 97.43% and the Under Curve Area which is 0.985.DOI : 10.29408/jit.v2i2.1489